Penugasan Aplikasi Penjualan Toko Kamera Menggunakan Visual Studio - Pratama, Refiansyah Galuh Rdha; Divansyah, Reza Choirudin; Basatha, Rizky (Lembaga Yasin AlSys, 2025)
In the ever-growing digital era, online sales applications have become an important solution for various types of businesses, including camera shops. This research aims to develop a sales application that makes it easier for customers to carry out transactions and makes it easier for shop owners to manage inventory and product marketing. This application is designed with main features such as product catalogs, search and filters, shopping baskets, promo notifications, as well as reviews and ratings from users. With the aim of improving the shopping experience, this application is expected to increase sales and customer loyalty. However, challenges such as intense competition, data security and quality of customer service need to be overcome to achieve success. It is hoped that the results of this research can make a positive contribution to the development of the camera shop business in the digital era.